Sex and Racial Disparities in Cardiac Rehabilitation Referral at Hospital Discharge and Gaps in Long‐Term Mortality. Issue 8 (6th April 2018) - Li, Shanshan; Fonarow, Gregg C.; Mukamal, Kenneth; Xu, Haolin; Matsouaka, Roland A.; Devore, Adam D.; Bhatt, Deepak L.
Abstract : Background: Cardiac rehabilitation (CR) referral is recommended for eligible patients, regardless of sex or race. It is unclear whether inequality in CR referral practices was associated with patients' long‐term survival. Methods and Results: We linked the American Heart Association Get With The Guidelines Coronary Artery Disease registry with Medicare claims data for 48 993 coronary artery disease patients from 365 hospitals across the United States between 2003 and 2009. We used generalized estimation equations to estimate the association between CR referral and mortality accounting for clustering within hospitals. Between 2003 and 2009, only 40% of eligible patients received CR referrals. Females were 12% less likely to receive CR referral compared with males. Black, Hispanic, and Asian patients were 20%, 36%, and 50% less likely, respectively, to receive CR referral than white patients. CR referral was associated with 40% lower 3‐year all‐cause mortality. Women and minorities who received CR referral at hospital discharge had significantly lower mortality compared with those who did not (odds ratios=0.61 [95% confidence interval, 0.56–0.66] for women, 0.75 [95% confidence interval, 0.63–0.88] for black, 0.62 [95% confidence interval, 0.50–0.79] for Hispanic, and 0.63 [95% confidence interval, 0.46–0.85] for Asian patients). Seven percent of the black versus white mortality gap could potentially be reduced by equitable CR referral. Conclusions: CR referral rates at hospital discharge remained low. Gaps in receiving CR referral at hospital discharge were large for women and minorities, and the mortality gap could potentially be reduced through elimination of inequality in CR referral.